Sobre el tiempo en mímesis: Ricoeur entre San Agustín y Martín Heidegger (Dossier: Mímesis desde América Latina) - Bastidas López, Diego Felipe (2019)
This article builds on the concept of Mimesis I in Paul Ricoeur’s proposal of the Triple Mimesis in Time and Narrative. To do so, the author looks into one of the concept’s three components: it’s temporal aspect. To do so, he traces the theoretical sources underlying the construction of a temporal dimension in Mimesis I, highlighting the discursive references that uphold the French philosopher’s argument, particularly in Saint Augustine’s Confessions and Martin Heidegger’s Time and Being. With this, he transits between the conception of temporal structures and the temporal logic that both Saint Augustine and Heidegger develop in relation to human actions, demonstrating the influence of these theoreticians in the constitution of the concept of Mimesis I; a necessary concept in Ricoeur’s theory for the analysis of narrative structures.